Pengaruh Intellectual Capital terhadap Pembiayaan Bermasalah Perbankan Syariah di Indonesia - Anggita Andini Saputri; Meilana Widyaningsih (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The research aims to determine and analyze the influence of intellectual capital (VACA, VAHU, STVA) on non-performing financing (NPF). Researchers are interested in conducting this research because Intellectual Capital is an interpretation of intangible assets as a source of work assessment which can influence problematic financing. Using quantitative methods and annual financial report data with 9 Islamic commercial banks for the 2018-2022 period. Data was processed using Eviews 10 with panel data regression analysis method. The research results show that simultaneously the variables VACA, VAHU, and STVA have a significant influence on problematic financing in Indonesia. Meanwhile, partially STVA does not have a significant effect on problematic financing in Indonesia. Meanwhile, VACA and VAHU have a significant influence on problematic financing in Indonesia.